2017
DOI: 10.1038/aps.2017.79
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces universal but differential drug resistance and impairs anticancer mechanisms of 5-fluorouracil in hepatoma cells

Abstract: Hepatocellular carcinoma (HCC) is one of the most refractory cancers. The mechanisms by which hypoxia further aggravates therapeutic responses of advanced HCC to anticancer drugs remain to be clarified. Here, we report that hypoxia (1% O) caused 2.55-489.7-fold resistance to 6 anticancer drugs (sorafenib, 5-fluorouracil [5-FU], gemcitabine, cisplatin, adriamycin and 6-thioguanine) in 3 HCC cell lines (BEL-7402, HepG2 and SMMC-7721). Among the 6 drugs, sorafenib, the sole one approved for HCC therapy, inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…It was reported that hypoxia confers sorafenib resistance in myeloid leukemia, renal, or gastric cancer cells 35 38 and is responsible for the acquired resistance to different anticancer drugs in HCC cells, including doxorubicin, etoposide, cisplatin, SN38, and 5-fluorouracil 39 43 . In fact, Liang et al 32 reported that the continued administration of sorafenib in HCC subcutaneous mouse tumor models increases the protein levels and transcriptional activity of HIF-1α.…”
Section: Hifs and Sorafenib Resistancementioning
confidence: 99%
“…It was reported that hypoxia confers sorafenib resistance in myeloid leukemia, renal, or gastric cancer cells 35 38 and is responsible for the acquired resistance to different anticancer drugs in HCC cells, including doxorubicin, etoposide, cisplatin, SN38, and 5-fluorouracil 39 43 . In fact, Liang et al 32 reported that the continued administration of sorafenib in HCC subcutaneous mouse tumor models increases the protein levels and transcriptional activity of HIF-1α.…”
Section: Hifs and Sorafenib Resistancementioning
confidence: 99%
“…Regarding MOC-6, several studies have demonstrated tumor progression associated with high oxygen consumption and lower blood supply in tumor microenvironment, and that hypoxia enhances resistance to antitumor drugs. Thus, under hypoxia, HepG2 cells were more resistant to cisplatin than under normal conditions [42], which could be due, at least in part, to the up-regulation of the ABC pumps induced by hypoxia that would reduce intracellular cisplatin concentration [43]. ADAM17 is a transmembrane metalloproteinase found overexpressed in a variety of human tumors.…”
Section: Mechanisms Of Hb Resistance To Platinum Derivativesmentioning
confidence: 99%
“…Unlike what happened with HepG2 cells, no differences were detected in the growth of the HepG2S1 and HepG2S3 lines between normoxia and hypoxia, which suggest that resistant cells display adaptive mechanisms related to hypoxic conditions. Hypoxia contribution to chemoresistance development in HCC has been described after the administration of drugs, such as 5-fluorouracil (5-FU) [25], doxorubicin, and cisplatin [26]. Involvement of hypoxic environment in the acquired resistance to sorafenib has also been reported in renal cancer [27,28], gastric cancer [29], and acute myeloid leukaemia [30].…”
Section: Discussionmentioning
confidence: 99%